Etiology and Outcomes of Acute Kidney Injury in Patients Admitted to a Single Tertiary Care Hospital: Balochistan Institute of Nephrology-Urology Quetta - Zarkoon, Abdul Kareem Zarkoon; Rind, Habib Ullah; Khan, Moin; Ahmed, Aijaz; Jakrani, Nasir; Hussain, Muhammad; Ali, Hamid; Haq, Mujeeb ul; Mandokhail, Abdul Ghaffar; Ullah, Atta; Khalil, Faiza; Hameed, Ghulam Muhammad., Abdul; et al. (Pakistan Journal of Kidney Diseases, 2021)
Acute kidney injury (AKI) is a common clinical syndrome with broad spectrum of etiologies and an important cause of morbidity and mortality requiring hospitalization. Depending on the cause and nature of AKI it may complicate to be life threatening or even proceed to Chronic Kidney disease (CKD) compromising the quality of life. Methods: The current retrospective study determines the causes and outcomes of AKI in patients of different age groups, who required hospitalization at our tertiary care hospital from March 2018 to March 2020. Possible etiologic conditions for AKI were recorded during the study period and AKI was classified according to the causes, age and outcome. Results: records of total of 267 patients with diagnosis of AKI were obtained who were admitted during the study period. Obstetric related diagnosis was the commonest reason for AKI (n= 50 18.7%), another 42 (15.7%) had obstructive nephropathy, prerenal AKI in 35 patients (13.1%) and other causes such as glomerulonephritis, sepsis, pigment nephropathy and drug related interstitial nephritis among others. Majority of the patients needed dialytic support, n=190 (71.2%) and majority of patients n=181 patients (67.7%) recovered completely, and only 11 patients (4.2%) expired. Conclusion: Our study reveals that majority of patients with AKI presenting to BINUQ had reversible causes of AKI with complete recovery in significant number of patients. Community wise programs to early detect AKI with prompt treatment will decrease the likelihood of such patients adding to the CKD population.